Circuit-Switched Voice Services Over HSPA - Ozturk, Ozcan; Kapoor, Rohit; Chande, Vinay; Jilei Hou; Mohanty, Bibhu (2010 IEEE 71st Vehicular Technology Conference, 2010)
Circuit-Switched (CS) Voice Services over HSPA (CSoHS) was recently introduced for 3GPP WCDMA Release 7/8 systems. The benefits of this feature include improving voice and data system capacity by utilizing the enhancements offered by the shared packet transport of HSPA air interface while preserving the already widely deployed core networks. In this paper, we discuss the operation and implementation of CSoHS and analyze its performance via simulations. We show that the system capacity of CSoHS is significantly higher than Release 99 CS voice under similar system conditions and voice quality.